Effect of eight weeks respiratory muscle training on respiratory capacity, functional capacity and quality of life on subjects with mild to moderate relapsing-remitting multiple sclerosis: A single-blinded randomized controlled trial - Ghannadi, Shima; Noormohammadpour, Pardis; Mazaheri, Reza; Sahraian, Mohammad Ali; Mansournia, Mohammad Ali; Pourgharib Shahi, Mohammad Hosein; Salmasi Fard, Amir Hesam; Abolhasani, Maryam (Multiple sclerosis and related disorders, 2022)
•Early stages of multiple sclerosis patients may have weak respiratory muscles.•The respiratory muscles' strength progress with inspiratory muscle training.•Inspiratory muscle training improves multiple sclerosis's fatigues. Multiple Sclerosis (MS) is a chronic inflammatory disease of the nervous system leading to muscle weakness, including the respiratory muscles that cause pulmonary complications, impair functional capacity, increased fatigue, and as a result decreases the quality of life. The purpose of the present study is to examine the influence of 8 weeks of respiratory muscle training (RMT) on pulmonary function and respiratory muscle strength in MS patients. The present study was a single-blind, randomized controlled trial that was conducted on 36 (27 Female, 9 Male) relapsing-remitting MS patients who were definitively diagnosed by a neurologist and randomly were divided into intervention and control groups. Both groups were educated on lifestyle modification with an emphasis on regular physical activity. In addition, the intervention group was prescribed eight weeks of respiratory muscle training with a threshold resistance device, daily, twice a day for three sets of 15 repetitions per set. Maximal expiratory pressure (PImax), maximal expiratory pressure (PEmax), spirometric indices, functional tests (six-minute walk test, timed up and go test), fatigue questionnaire, and questionnaire of quality of life were assessed before and after trials. A total of 36 patients (75% female; mean age 38.00(8.86) years; BMI 26.56(2.64) kg/m2) were included in the study. The strength of inspiratory and expiratory muscles, respiratory function, fatigue, and quality of life were significantly improved in the intervention group (p<0.005). In addition, there was a significant improvement in the rate of fatigue and quality of life in all their dimensions (p<0.005). Only in the six-minute walk test, no significant improvement was seen in the intervention group compared to the control group (p = 0.262). Findings could help therapists to provide MS patients with more effective respiratory muscle training protocols to maximize the benefits of rehabilitation.